2020
DOI: 10.1021/acs.chemrestox.9b00382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trichloroethylene on the Expression of Long Intergenic Noncoding RNAs in B6C3F1 Mouse Liver

Abstract: Trichloroethylene (TCE), a widely used industrial solvent, is a common environmental contaminant. We previously reported that TCE-induced changes in DNA methylation and miRNA expression contributed to the development of a liver tumor in mice. In this study, we investigated the role of long intergenic noncoding RNA (LincRNA), another type of epigenetic modification, in TCE hepatocarcinogenesis. Male B6C3F1 mice were gavaged with TCE at dose levels of 0, 100, 500, and 1000 mg/kg b.w. for 5 days. The expression c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Intracellular lncRNAs are known to suppress the biological activity of miRNAs and regulate the expression of mRNAs targeted by miRNAs through competing endogenous RNAs (ceRNAs) ( 11 ). Therefore, lncRNAs have been considered to be important targets for treating multiple diseases ( 12 , 13 ). Moreover, lncRNAs play key roles in malignant tumors, including liver cancer ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular lncRNAs are known to suppress the biological activity of miRNAs and regulate the expression of mRNAs targeted by miRNAs through competing endogenous RNAs (ceRNAs) ( 11 ). Therefore, lncRNAs have been considered to be important targets for treating multiple diseases ( 12 , 13 ). Moreover, lncRNAs play key roles in malignant tumors, including liver cancer ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational medicamentosa‐like Dermatitis induced by Trichloroethylene (OMDT) may occur in some occupational workers exposed to TCE (Li et al, 2019). In recent years, many studies have found that OMDT patients not only present with severe systemic skin damage, but are also accompanied by multiple organ damage such as heart, liver, and kidney, liver injury is one of the main causes of death (Iritas et al, 2021; Ren et al, 2020). However, the pathogenesis of liver injury is unclear, which seriously restricts the treatment and prevention of OMDT.…”
Section: Introductionmentioning
confidence: 99%
“…liver, and kidney, liver injury is one of the main causes of death (Iritas et al, 2021;Ren et al, 2020). However, the pathogenesis of liver injury is unclear, which seriously restricts the treatment and prevention of OMDT.…”
mentioning
confidence: 99%
“…Previous reports have indicated the importance of lncRNAs in modulating cancer-related signaling pathways (12,13). Moreover, lncRNAs may be related with types of malignant tumors and serve as key factors for tumorigenesis of many cancers (14).…”
Section: Introductionmentioning
confidence: 99%